Flexible MoS2-Polyimide Electrode for Electrochemical Biosensors and Their Applications for the Highly Sensitive Quantification of Endocrine Hormones: PTH, T3, and T4 - Kim, Hyeong U.; Kim, Hye Youn; Seok, Hyunho; Kanade, Vinit; Yoo, Hocheon; Park, Kyu Young; Lee, Jae Hyun; Lee, Min Ho; Kim, Taesung (Analytical Chemistry, 2020)
Flexibile biosensors have a lot of applications in measuring the concentration of target bioanalytes. In combination with its flexibility, electrochemical sensors containing 2D materials have particular advantages such as enlarged area compatibility, transparency, and high scalability. A flexible biosensor was fabricated by direct synthesis of molybdenum disulfide (MoS2) on a polyimide (PI) substrate, which can be used as the working electrode in electrochemistry platforms. The direct formation of 2D-MoS2 on the PI was achieved using plasma-enhanced chemical vapor deposition (PE-CVD). Since the MoS2 provides higher electrical conductivity, the MoS2-Au-PI flexible sensor is able to provide highly sensitive detection of target proteins with a relatively fast response via cyclic voltammetry. To evaluate the high performance of the fabricated sensor, we selected the endocrine-related hormones parathyroid hormone (PTH), triiodothyronine (T3), and thyroxine (T4) as analytes because they are one of the most important markers for the determination of endocrinopathy, however, they are very difficult to quantify. The newly developed biosensor achieved highly sensitive detection of the hormones and could determine their location with high accuracy. In addition, we performed electrochemical measurements of hormones obtained from 30 clinical patients' sera with confirmed agreement and compared with the measurements performed with standard immunoassay equipment (E 170, Roche Diagnostics, Germany).
Keywords: Electrical conductivity; Electrochemical biosensor; Electrochemical measurements; Fabricated sensors; Highly sensitive detections; Molybdenum disulfide; Parathyroid hormones; Plasma enhanced chemical vapor depositions (PE CVD)